2019
DOI: 10.4236/msce.2019.711006
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Hydroxide Zinc Carbonate Composite for Supercapacitors

Abstract: Energy density and production cost for high-performance electrode materials are the main challenge for the capacitive storage technology. In this paper, novel Hydroxide Zinc Carbonate (Zn 4 CO 3 (OH) 6 ·H 2 O, HZC) catalyst layers, which are composed of irregular stagger arrangement nanosheets, have been synthesized successfully on foam Ni from inorganic precursors by a feasible in situ hydrothermal method. Measured by electrochemical tests as electrode materials for supercapacitors, the HZC@Ni foam show high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[1] Among these devices, the supercapacitor has attracted more attention due to its wide range of applications, notably in the fields of electric vehicles, space equipment, mobile electronic devices, and many other common electronic devices. [2][3][4] In supercapacitors, the specific capacitance is primarily associated with the formation of an electric double layer (EDL) at the electrode/electrolyte interface. Additionally, for certain materials, pseudo-capacitance resulting from faradic processes can contribute significantly to the overall specific capacitance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Among these devices, the supercapacitor has attracted more attention due to its wide range of applications, notably in the fields of electric vehicles, space equipment, mobile electronic devices, and many other common electronic devices. [2][3][4] In supercapacitors, the specific capacitance is primarily associated with the formation of an electric double layer (EDL) at the electrode/electrolyte interface. Additionally, for certain materials, pseudo-capacitance resulting from faradic processes can contribute significantly to the overall specific capacitance.…”
Section: Introductionmentioning
confidence: 99%
“…That is why intensive research efforts have been undertaken in recent years to advance electricity storage technologies [1] . Among these devices, the supercapacitor has attracted more attention due to its wide range of applications, notably in the fields of electric vehicles, space equipment, mobile electronic devices, and many other common electronic devices [2–4] . In supercapacitors, the specific capacitance is primarily associated with the formation of an electric double layer (EDL) at the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc (Zn) is a transition metal which forms oxides and hydroxides with various elements. Zn-based nanocomposites can be used as an electrode material for supercapacitors because they have excellent electrochemical properties and are inexpensive [28,29]. To remove toxic gases, zinc carbonate compounds are used in respirators [30].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxide zinc carbonate composite electrode (HZC) has been synthesized in our previous studies, which showed novel electrochemical activity in high concentration KOH electrolyte [9]. However, higher concentration of KOH will undoubtedly increase the corrosion of electrodes and equipment, which is unfa- Active carbon (AC, BP2000), acetylene black and PTFE mixed together with mass proportion of 8:1:1, using ethanol as dispersant.…”
Section: Introductionmentioning
confidence: 99%